2016
DOI: 10.3389/fncom.2016.00042
|View full text |Cite
|
Sign up to set email alerts
|

Burst Firing Enhances Neural Output Correlation

Abstract: Neurons communicate and transmit information predominantly through spikes. Given that experimentally observed neural spike trains in a variety of brain areas can be highly correlated, it is important to investigate how neurons process correlated inputs. Most previous work in this area studied the problem of correlation transfer analytically by making significant simplifications on neural dynamics. Temporal correlation between inputs that arises from synaptic filtering, for instance, is often ignored when assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…While a single spike may not pass through a synapse, multiple spikes in a burst will cross the synapse more reliably, improving the possibility of eliciting postsynaptic spikes. Besides, some studies reported that the correlation strength between neurons could be enhanced through the bursts rather than individual spikes [ 29 , 30 ]. The bursting activity can efficiently enhance the transfer of information either by storing information in the burst or by strengthening the connection with other neurons.…”
Section: Discussionmentioning
confidence: 99%
“…While a single spike may not pass through a synapse, multiple spikes in a burst will cross the synapse more reliably, improving the possibility of eliciting postsynaptic spikes. Besides, some studies reported that the correlation strength between neurons could be enhanced through the bursts rather than individual spikes [ 29 , 30 ]. The bursting activity can efficiently enhance the transfer of information either by storing information in the burst or by strengthening the connection with other neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al ( 2016 ) address the interaction between input and output correlations for different synaptic dynamics using numerical simulation of a pair of neurons. They find that slow synaptic filtering lead to bursts in the output, which results in increased output correlation and synchrony on longer time-scales.…”
Section: About This Frontiers Topicmentioning
confidence: 99%
“…The responses we generated in the previous part are assumed to describe conductances. To obtain the firing rate of the ORNs from its input conductances, we approximated the dynamics of a neuron by the conductance-based leaky integrate-and-fire model with adaptation (Richardson and Gerstner, 2005;Chan et al, 2016).…”
Section: Obtaining the Instantaneous Firing Rate Of Neuronsmentioning
confidence: 99%
“…While we do add external noise to ORNs, for the purpose of obtaining realistic response latencies as described in the next section, and PNs, for the purpose of mimicking their spontaneous activity, the noise effects are small and only visible at low stimulus concentrations. The general effects of noise on neural response and correlation have been well studied (Shadlen and Newsome, 1998;Brunel et al, 2001;Ostojic et al, 2009;Chan, 2015;Chan et al, 2016) and are beyond the scope of this study.…”
Section: Comparison Between Orn and Pn Responsementioning
confidence: 99%